Effect of silica fume on compressive strength of ultra-high-performance concrete made of calcium aluminate cement/fly ash based geopolymer. (15th December 2022) - Wang, Fang; Sun, Xiaokun; Tao, Zhong; Pan, Zhu
Abstract: The study on geopolymers blended with silica fume is scant. This study investigates the effects of silica fume (SF) on the compressive strength of geopolymer-based ultra-high-performance concrete (G-UHPC) subject to ambient curing. Low-calcium fly ash (LCFA) and calcium aluminate cement (CAC) were activated by a combination of sodium hydroxide and sodium silicate solution to produce geopolymer binders. Effects of the CAC content, alkaline solution to binder (A/B) ratio, and sodium hydroxide (SH) concentration on the flowability and compressive strength of geopolymer binders were studied. The SF dosage varied from 5% to 30% of the total binder weight, and the Taguchi method was used to determine the optimum mix proportions. The incorporation of SF showed a complicated influence on the compressive strength, depending on the CAC content. For mixes with 20% CAC content, the compressive strength increased with increasing SF dosage. But for mixes with 10% CAC content, a high SF dosage (>10%) negatively influenced the compressive strength. The mechanisms for this contradictory behavior were discussed based on the X-ray diffraction and scanning electron microscopy analyses. The inclusion of steel fibers has a positive influence on the mechanical properties of G-UHPC. The G-UHPC mix with 1.5 vol% steel fibers achieved a compressive strength of 139.1 MPa and flexural strength of 13.5 MPa at 28 days. Highlights: Geopolymer-based UHPC was developed by incorporating calcium aluminate cement. Taguchi analysis was used to optimise mixture compositions for geopolymer-based UHPC. Effects of silica fume on the strength were explained via SEM and XRD analyses. Effects of steel fiber on the mechanical properties were evaluated.